THE INFLUENCE OF ASSET AND PROFITABILITY TOWARD SHARE VALUE: MEDIATION EFFECT OF LIQUID ASSET - Tigor Sitorus; * Denny (Copernican Journal of Finance & Accounting, 2018)
The purpose of this research is to extend the relationship between asset and profitability with share value and this study also aims to find out the factors that influence of the value of share and propose the Liquid Asset as the intervening variable for filling the gap of prior research within the mining sector listed on the Indonesian Stock Exchange from the period of 2010 to 2014. This research used quantitative approach with a descriptive method by using secondary data in the form of financial report of the mining sector. The population in this study is all mining sector companies listed on the Indonesian Stock Exchange. The sample was taken using purposive sampling method and obtained 20 companies that met the criteria of sampling, while the observational data that could be collected was 100 within 2010–2014 (5years). This research used the data analysis method of Structural Equation Modelling path. The results of this study prove that all hypotheses are accepted, so it can be concluded that the result evidently shows that the Liquid Asset is able to mediate the influence of asset and profitability toward value of share.